Umowy normalizujące stosunki między Państwem Izrael a Zjednoczonymi Emiratami Arabskimi i Królestwem Bahrajnu w świetle prawa międzynarodowego – wybrane zagadnienia - Łyżwiński, Maciej (Kortowski Przegląd Prawniczy, 2021)
The main purpose of this article is to analyse the normalization agreements between the State of Israel and the United Arab Emirates and the Kingdom of Bahrain (known as the Abraham Accords). First of all, author wants to present these treaties in the light of international law. This article contains a detailed description of provisions of the agreements based on examples of theory and practice of international law. Moreover, it presents the legal nature of the treaties, as well as the historical context of their conclusion. The author concluded that international law guarantees peace and gives hope for a better future. The Abraham Accords are an example of the creation of this law.